Correlation of Stress Levels and the Incidence of Pityriasis Sicca in Final Year Students of the Faculty of Medicine, Universitas Sumatera Utara Class of 2017 - Marlina; Sinaga, Riana Miranda (Talenta Publisher, 2021)
Background: Pityriasis sicca is a non-inflammatory skin disorder. The symptoms such as white or gray scales that accumulate on the surface of the scalp or in a localized place, peels easily and usually with itching. There are three main factors that cause Pityriasis sicca. Stress stimulates the body to increase sebum production in the sebaceous glands. Objective: To know the correlation between stress levels and incidence of Pityriasis sicca in the final year students of the Faculty of Medicine, Universitas Sumatera Utara class of 2017. Methods: This was an analytical study with a cross-sectional design, started from July 2020 until October 2020. Sampling was carried out using a total sampling technique. The data were obtained using univariate and bivariate statistical analysis. Results: Univariate analysis showed 102 respondents were at a normal stress level (40.3%) and there were 105 respondents (41.5%) who suffered from Pityriasis sicca, total samples were 253 respondents. From the bivariate analysis, it was found that there is a significant correlation between stress levels and the incidence of Pityriasis sicca. Conclusion: There is correlation between stress levels and the incidence of Pityriasis sicca in class 2017 students of the Faculty of Medicine, Universitas Sumatera Utara.